The Construction of Oven Designed by Heat Exchanger in Drying Porang at SME Coco Prima - Sebayang, Kerista; Ginting, Herli; Andriayani, Andriayani; Harahap, Agus Salim (Talenta Publisher, 2019)
The small-medium enterprise (SME) Coco Prima has been under nurtured of LPPM USU since 2018. Ever since, it has been improving its productivity and diversifying its productivity into drying products. Currently, this SME manages porang as one of new export commodity. The problem faced by partners is a large and fast drying methodology. Porang or iles-iles are rotten raw materials that only last for three days after harvesting due to the unpleasant odors resulted more than three days, and subsequently, they cannot be processed. Drying under sunlight requires to four days reaching about 70% degree of dryness. Due to unfavorable weather conditions, the raw material becomes sweaty and moldy and produces black colour and soft textures. Therefore, a 3x3x2 cubic meter of drying oven has been constructed along with shelves and heat exchanges supported by liquid petroleum gas (LPG) gas. The heat exchange is designed accordingly to provide lower temperature in the oven, so that the air pressure within it is more efficient and less heat is wasted during reheating process. The heating is sufficient by using LPG and fan 18’. The oven is consisted of two layers in which between the layers are given glass wool as a heat barrier to the environment. It is also designed with a small vent exactly on the middle of the top with the intention to flow water vapour out from the vent, while the cold air is touched by that water vapour in the oven, it converts downward on the heat exchanger repeatedly. From this applied system, 750 kg iles-iles was heated within two days with a tube-of-12 kg LPG gas.